AJAX AND OTHER OBJECTS: HOMER'S VIBRANT MATERIALISM. (27th November 2015) - Purves, Alex
Abstract : ἕρϰος Ἀχαιῶν: ἔμψυχον τεῖχος τῶν Ἑλλήνων. Bulwark of the Achaeans: living wall of the Greeks. Schol. D. Il. 6.5 (on Ajax) Now, still breathing, he is simply matter… Simone Weil, 'The Iliad or the Poem of Force' The two quotations at the start of this paper, one from the D scholion on the Iliad and the other from Simone Weil's famous essay on force, both make of the Homeric warrior a kind of 'breathing material'. Two references, then, to the liveliness of objects, but each meaning very different things. For the scholiast places man on the same side as materiality, as if humans and things can equally be infused with life and can exist in a sort of continuum, but Weil argues that a human who is reduced to mere matter, even if he is a still a thing that breathes, is as good as nothing. Unlike the scholiast, Weil's interpretation is predicated on a strong belief in the duality of body and soul in the structure of human life, and since objects do not have souls they are, for her, essentially dead. Throughout her essay, Weil visits again and again the materiality of Homeric man and his propensity to turn, under the crushing power of force, into what she calls alternately a 'thing', 'inert matter', 'stone', and even 'nothingness'. But for the D scholiast, the comparison of Ajax to stone does not subjugate him or turn him into a 'mere' or 'inert' object. On the contrary, the gloss ἔμψυχον τεῖχος speaks instead to the lively and permeable boundary between human and nonhuman in early Greek epic, one that suggests that objects can have their own life form, their own energy, vitality, and even creativity.